Data analytics on Yelp data set - Tata, Maitreyi (Kansas State University, 2017)
In this report, I describe a query-driven system which helps in deciding which restaurant to invest in or which area is good to open a new restaurant in a specific place. Analysis is performed on already existing businesses in every state. This is based on certain factors such as the average star rating, the total number of reviews associated with a specific restaurant, the price range of the restaurant etc. The results will give an idea of successful restaurants in a city, which helps you decide where to invest and what are the things to be kept in mind while starting a new business. The main scope of the project is to concentrate on Analytics and Data Visualization.
Keywords: Data analytics; Data visualization